Genetic and epigenetic changes in malignant cells of tumors of urogenital organs - Gordiyuk, V.V. (Вiopolymers and Cell, 2010)
More than 90 % of human malignant neoplasms are presented by epithelial tumors. Cancer of urogenital organs is a serious problem because of wide spread of disease and high mortality rates. Tumorogenesis is associated with different defects of genetic apparatus of cells as well as epigenetic factors (DNA methylation disorders, chromatin reorganizations in processes of histones modifications, regulation of gene expression with small non-coding RNAs). In this review we analyzed genetic and epigenetic changes in the urogenital tumors.